2016
DOI: 10.1093/nar/gkw815
|View full text |Cite
|
Sign up to set email alerts
|

Long-range correlations in the mechanics of small DNA circles under topological stress revealed by multi-scale simulation

Abstract: It is well established that gene regulation can be achieved through activator and repressor proteins that bind to DNA and switch particular genes on or off, and that complex metabolic networks determine the levels of transcription of a given gene at a given time. Using three complementary computational techniques to study the sequence-dependence of DNA denaturation within DNA minicircles, we have observed that whenever the ends of the DNA are constrained, information can be transferred over long distances dire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 58 publications
(70 reference statements)
6
67
0
Order By: Relevance
“…The four DNA sequences chosen for this study ((AA)12, (AT)12, (GG)12 and (CG)12) enable us to interrogate not only the impact of the overall GC/AT ratio but also the impact of the bp-order, which causes different strengths on stacking interactions, being these critical for DNA stability. Overall, ATrich sequences show higher propensity to melt compared with CG-rich sequences in agreement with previous studies [15], [23], [24], [36], although striking differences are found whether sequences contain RY and YR intra-strand stacking or YY and RR. Poly-d(C) appears to be significantly more resistant than the other G-rich sequence, polyd(CG), because the former is the sole sequence that do not form melting bubbles for any supercoiling density, and the latter presents denaturation for all torsional constraints.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The four DNA sequences chosen for this study ((AA)12, (AT)12, (GG)12 and (CG)12) enable us to interrogate not only the impact of the overall GC/AT ratio but also the impact of the bp-order, which causes different strengths on stacking interactions, being these critical for DNA stability. Overall, ATrich sequences show higher propensity to melt compared with CG-rich sequences in agreement with previous studies [15], [23], [24], [36], although striking differences are found whether sequences contain RY and YR intra-strand stacking or YY and RR. Poly-d(C) appears to be significantly more resistant than the other G-rich sequence, polyd(CG), because the former is the sole sequence that do not form melting bubbles for any supercoiling density, and the latter presents denaturation for all torsional constraints.…”
Section: Discussionsupporting
confidence: 92%
“…The effect of torque on simulated linear DNA structures has been relatively underexplored in comparison. By imposing torsional constraints, simulations have shown that unwounded DNA has a greater predisposition to form melting bubbles compared to relaxed DNA, with this propensity being strongly dependent on sequence: denaturation was only observed on an (AT)3 segment in linear DNA [23] and prominently in AT-rich areas in undertwisted small DNA circles between 60-110 bp [24]. Modelling an infinite linear tract of DNA upon undertwisting showed that DNA partitions its perturbations such that there are regions of extreme disruption in coexistence with regions which remain relatively close to the canonical B-form DNA structure, and that this is sequence-dependent [25].…”
Section: Introductionmentioning
confidence: 99%
“…There is a good overall agreement between the direct computation of the persistence lengths and Eqs. (18) and (19) (with the plateau values of Fig. 4), for both oxDNA1 and oxDNA2.…”
Section: Stiffness Matrixmentioning
confidence: 78%
“…Even though these models and tools are generally implemented as freely available and open software packages, the burden of passing from one representation to the other is typically on the end user, making the process not only laborious but also prone to errors. In addition, the lack of interoperability hinders the wider adoption of each model or simulation tool and is especially detrimental to researchers interested in multiscale modeling spanning multiple spatial and temporal scales …”
Section: Introductionmentioning
confidence: 99%